Inoperable infiltrative basal cell carcinoma successfully treated with vismodegib. Issue 4 (19th June 2017) - Zargari, Omid; Azimi, Seyyede Zeinab; Geranmayeh, Siamak
Abstract: Basal cell carcinoma (BCC) is the most common skin cancer but usually has a good prognosis. However, there is a subset of BCC cases with a less favorable prognosis. For patients with locally advanced, recurrent or metastatic BCCs who are not suitable for surgery or radiotherapy, small‐molecule drug inhibitors of hedgehog pathway are a new therapeutic opportunity. Here, we present a case of infiltrative BCC with multiple recurrences. Wide excision with reconstructive plastic surgery was performed initially with adjuvant radiotherapy. Due to multiple recurrences afterward, radiotherapy, topical imiquimod and oral itraconazole were used but were not effective. Finally, the patient was treated with vismodegib which led to a complete response. Moreover, the patient's symptoms due to the locally diffused cancer resolved.